And the Spirit Moved Them : The Lost Radical History of America's First Feminists - Hunt, Helen LaKelly (Book collections on Project MUSE., 2017)
This account of faith and solidarity excavates the forgotten radical activism that confronted race and gender in pre-Civil War America.